2015
DOI: 10.1007/s40825-015-0030-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Low-T NH3-SCR Activity of a Commercial Fe-Zeolite Catalyst by NH4NO3 Dosing: an Experimental and Modeling Study

Abstract: The potential improvement of DeNOx efficiency enabled by injecting calibrated amounts of NH 4 NO 3 (AN) aqueous solution into lean engine exhausts prior to NH 3 -SCR converters (Enhanced-SCR) has been investigated by dynamic and steady-state catalytic activity runs over a commercial Fe-zeolite monolith catalyst. The study was performed varying GHSV (35,000-100,000 h −1 ), temperature (150-550°C), as well as AN and NO 2 feed concentrations. The results demonstrate that already at low temperature (180°C) the DeN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Recently, it was found that surface ammonia nitrates play a significant role in “fast” SCR reaction. Multiple reaction steps including ammonia nitrate formation, ammonia nitrate titration by NO, and ammonia nitrate decomposition are involved in the “fast” SCR mechanism. In order to accurately describe the fast and NO 2 SCR reactions, significant effort involving modeling of NO 2 adsorption, desorption. and interaction between ammonia nitrates and NO is needed.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was found that surface ammonia nitrates play a significant role in “fast” SCR reaction. Multiple reaction steps including ammonia nitrate formation, ammonia nitrate titration by NO, and ammonia nitrate decomposition are involved in the “fast” SCR mechanism. In order to accurately describe the fast and NO 2 SCR reactions, significant effort involving modeling of NO 2 adsorption, desorption. and interaction between ammonia nitrates and NO is needed.…”
Section: Resultsmentioning
confidence: 99%
“…A stable carbon framework is formed when the pyrolysis final temperature is raised to 850°C continuously, and the original active sites on the surface are stable and deactivate due to the high temperature. Therefore, the decrease of the specific surface area is not obvious after the denitration [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…2NH 3 + 2NO + NH 4 NO 3 = 3N 2 + 5H 2 OHere, NH 4 NO 3 can simply be regarded as a masked NO 2 molecule and negates the need for the kinetically relevant oxidation of NO by O 2 under standard SCR conditions. 11 Ensuing work by Tronconi et al 16 proved this by demonstrating the equivalence of NO 2 and NH 4 NO 3 through comparison of their respective SCR rates, both of which were far beyond those of standard SCR.…”
Section: Introductionmentioning
confidence: 93%
“…Table 1 summarizes possible SCR pathways that have been suggested by others. 15,16,20,21 Please note that these are known net gas phase reactions and not elementary steps occurring on a surface. The reaction network N (1) and N (2) represent standard SCR pathways; they differ in the way that nitrous acid (HNO 2 ) is formed which is regarded as the key intermediate leading to N 2 formation.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%